Menjaga Berkah di Era Digital: Strategi Perbankan Syariah Menghadapi Disrupsi AI dan Gen-Z - Awaluddini Marifatullah; Lika Akana Helmi; Abdul Rahim (Fakultas Syariah IAIN Kerinci, 2026)
The integration of Artificial Intelligence (AI) and the expansion of Generation Z (Gen-Z) pose dual challenges and transformative opportunities for the Islamic banking industry. This study aims to formulate a digital strategy to maintain Sharia compliance and market competitiveness. Using a descriptive-qualitative library research approach, this paper evaluates technology adoption through TAM, UTAUT, Institutional Theory, and Maqashid al-Shariah frameworks. The findings highlight a critical market mismatch: while Gen-Z accounts for 24.93% of Indonesia's 284.67 million population, the Islamic banking market share stagnates at 7.51% due to low financial literacy. As digital natives, Gen-Z demands high performance expectancy, rapid access, and robust cybersecurity to prevent data breaches. Consequently, this study proposes a